Water stress in commercial potato (Solanum tuberosum L.) cultivars in the central region of Peru - Perez, Emmanuel (2024)
Potato (Solanum tuberosum L.) is a crop of great importance worldwide due to its high nutritional value and its adaptability to different climatic conditions. In Peru, it is one of the main crops in terms of production and consumption, with Junín being one of the departments with the highest production. The aim of this research was to evaluate the effect of water stress on the growth and yield of commercial potato cultivars. Four irrigation frequencies (field capacity, every 7, 14 and 21 days) and five commercial potato cultivars (Canchán, Yungay, Wankita, Serranita and Shulay) were evaluated, distributed in a completely randomized design with a 5x4 factorial arrangement, with five replications. It was installed under greenhouse conditions and seven variables (plant emergence, plant height, number of stems, number and weight of tubers, transpiration rate and dry matter) were evaluated. The results showed statistical differences in all the variables evaluated. It was found that the Canchán cultivar with irrigation frequency every 21 days was more tolerant to drought with an average rate of 0.69 ml, the maximum permissible irrigation limit in greenhouse is every 14 days. The highest number of tubers was observed in the Wankita cultivar with 29.8 tubers under a drought stress of 14 days. The highest tuber weight was obtained with the Yungay cultivar at field capacity with 0.438 kg per plant. It is concluded that water stress influences potato growth and production.